Inhibitive effect of polyacrylamide grafted with fenugreek mucilage on corrosion of mild steel in 0.5 M H2SO4 at 35°C - Srivastava V.; Banerjee S.; Singh M.M. (My University, 2025)
The inhibitive effect of polyacrylamide grafted with fenugreek mucilage, a natural grade polysaccharide, on the corrosion of mild steel in 0.5M H 2SO4 has been investigated by weight loss, potentiodynamic polarization and electrochemical impedance spectroscopy. An inhibition efficiency of 78% has been obtained at a concentration as low as 1 ppm and efficiency as high as 96% at 100 ppm. The polarization studies reveal that it acts as a predominantly cathodic inhibitor. The adsorption of this inhibitor on the mild steel surface obeys a Langmuir adsorption isotherm. The deposited films on the electrode surface have been analyzed by using microscopic techniques. © 2009 Wiley Periodicals, Inc.